Factors Associated with Surveillance for Early Detection of Hepatocellular Carcinoma in Liver Cirrhosis Patients - Ario Perbowo Putra; Andri Sanityoso Sulaiman; Juferdy Kurniawan; Kuntjoro Harimurti (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Background: Minimal number of KHS patients diagnosed through surveillance is thought to be the cause of continued low survival. It is important knowing the proportion of surveillance for early detection of KHS in patients with liver cirrhosis and related factors.Objective: Determine the proportion of surveillance for early detection of KHS in patients with liver cirrhosis and related factors.Method: Cross-sectional study of patients with liver cirrhosis at RSCM from January to December 2013. Data obtained from medical records and reconfirmed by telephone. Surveillance is required for abdominal ultrasound with or without AFP at least once a year within 3 years after that period. Factors studied were gender, ethnicity, education level, income level, availability of medical assurance, location of residence, surveillance education, cirrhosis etiology, and severity of cirrhosis. Then logistic regression test is used in the multivariate analysis.Results: From 200 patients, 50 patients (25,0%) underwent surveillance, 150 patients (75,0%) did not. Bivariate analysis resulted in 4 variables with p 0.25, gender (p = 0,056), ethnicity (p = 0, 231), surveillance education (p = 0,005), and severity of cirrhosis (p = 0, 005). Multivariate analysis resulted risk factors for surveillance were surveillance education (OR = 2,598; CI 95% (1,325 - 5,094), p = 0,005) and severity of cirrhosis (OR = 1.815; CI 95% = 1,210-2,724; p = 0,004).Conclusion: Surveillance education and severity of cirrhosis are factors associated with surveillance for early detection of KHS in liver cirrhosis patients.